Perkembangan Kemandirian pada Anak Usia Dini di TK Amarta Tani HKTI Bandar Lampung - Sulistianah, Sulistianah; Tohir, Ahmad (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2020)
The aims of this research was to describe the development of independence in early childhood. In more detail, an overview, and description of independent abilities is obtainde 3 children at TK Amarta Tani HKTI Bandar Lampung. This research was conducted in class B2 at TK Amarta Tani HKTI Bandar Lampung. This research used a qualitative approach, with 3 children as the subject. Collecting data using the method of ebservation, unstructured interviews, and documentation. Data analysis and validity test used triangulation. Based on the results of research conducted at TK Amarta Tani HKTI Bandar Lampung, KYA has not been independent in the aspects of development of emotional and cognitive independence, MS still has not show independence in the aspects of emotional independence, and MA is not yet independent in the aspects of cognitive independence.